2013
DOI: 10.3109/00016357.2013.822547
|View full text |Cite
|
Sign up to set email alerts
|

Complex analysis of multiple single nucleotide polymorphisms as putative risk factors of tooth agenesis in the Hungarian population

Abstract: This complex analysis shows the important role of PAX9 and MSX1 SNPs and of their interactions in tooth agenesis, while IRF6, FGFR1 and AXIN2 SNPs had no detectable role in the Hungarian population. These results also reveal that risk factors in hypodontia need to be identified in various populations, since there is considerable variability among them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The findings indicated a synergic effect of the 2 polymorphisms. In all 3 studies, these polymorphisms are termed “G‐1031A” in the case of rs2073244 and “T‐912C” in the case of rs2073246 . There appears to be, however, no specified reference sequence given according to which the polymorphisms were aligned, nor is there any information on the point from where the numbering starts.…”
Section: Mutations and Polymorphisms In The Pax9 Genementioning
confidence: 99%
“…The findings indicated a synergic effect of the 2 polymorphisms. In all 3 studies, these polymorphisms are termed “G‐1031A” in the case of rs2073244 and “T‐912C” in the case of rs2073246 . There appears to be, however, no specified reference sequence given according to which the polymorphisms were aligned, nor is there any information on the point from where the numbering starts.…”
Section: Mutations and Polymorphisms In The Pax9 Genementioning
confidence: 99%
“…however, this was not significant after adjusting for sex, ethnicity and multiple testing ( to play a role in hypodontia. 8,11,23,24,30 A meta-analysis of current findings with previous findings 10 suggests that common variants of the EDA gene are associated with non-syndromic hypodontia in Europeans. On the other hand, no association between hypodontia and any of the SNPs of PAX9, MSX1 and AXIN2 genes was found.…”
Section: Re Sultsmentioning
confidence: 54%
“…33 Rare variants of PAX9 were reported to be associated with molar agenesis; 31 since then, several studies have identified either rare or common variants of PAX9 in different populations, especially in relation to the agenesis of maxillary lateral incisors. 10,17,23,34,35 Using a relatively large sample of unrelated individuals, a higher proportion of the A-allele of the rs2073242 SNP was found in cases than in controls, but the difference was not statistically significant. While other studies have not investigated this particular SNP, noteworthy differences in genotype frequencies for other SNPs (rs2073246 and rs2073244) have been reported between controls and patients with tooth agenesis.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations